2018
DOI: 10.18203/2320-1770.ijrcog20183339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of counselling on selecting a hormonal contraceptive method

Abstract: INTRODUCTIONUnmet need for family planning is an important indicator for assessing the demand for family planning services. As per the national family health survey (NFHS-4), the contraceptive prevalence rate in women age 15-49 years was 53.5 % and the unmet need for family planning among married women was 12.9 %. The contraceptive usage patterns vary widely in India with prevalence of modern contraception reported to be 47.8 %, which ABSTRACTBackground: Unmet need for family planning is an important indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Various other studies also showed that maximum deaths were due to direct cause but Sreekumari et al in their study found that indirect cause predominated and amounted to 50.49% while direct causes accounted for 42.57% deaths. 4,6,[8][9][10]13,14 In our study, direct obstetric deaths (73.68%) include deaths from haemorrhage 29.47%, PIH 28.42%, sepsis 9.47% and thromboembolism 6.31%. Even today, a large number of maternal deaths is due to the classical triad of haemorrhage, PIH and sepsis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Various other studies also showed that maximum deaths were due to direct cause but Sreekumari et al in their study found that indirect cause predominated and amounted to 50.49% while direct causes accounted for 42.57% deaths. 4,6,[8][9][10]13,14 In our study, direct obstetric deaths (73.68%) include deaths from haemorrhage 29.47%, PIH 28.42%, sepsis 9.47% and thromboembolism 6.31%. Even today, a large number of maternal deaths is due to the classical triad of haemorrhage, PIH and sepsis.…”
Section: Discussionmentioning
confidence: 69%
“…5 Patel et al observed a higher mean MMR of 413.3/100,000 live births. 6 In More than half (70.52%) of maternal deaths occurred in post-partum period and included 36.84% deaths after vaginal delivery and 33.68% deaths after LSCS. Antenatal women constituted 29.46% of all maternal deaths and included 10.52% of early pregnancy deaths (septic abortions and ectopic deaths).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefit of family planning and contraceptive, uptake of contraceptives among adolescents is affected by numerous socio-cultural and demographic factors [15,16] which includes cultural beliefs, peer influence, religion, and fear of side effects [17,18] father's educational background and prior discussion of contraceptive use with a partner [19,20] age of adolescent, education, work status, knowledge of ovulatory cycle, visit of health facility, non-youth-friendly health services and marital status [21,22] spouses or partners made the decision for them to utilize contraception [23]. Other health-related factors reported includes counselling on contraceptive and health provider attitudes [24,25].…”
Section: Introductionmentioning
confidence: 99%